Randomized Phase II Study of the X-linked Inhibitor of Apoptosis (XIAP) Antisense AEG35156 in Combination With Sorafenib in Patients With Advanced Hepatocellular Carcinoma (HCC). (December 2016) - Lee, Francis A.S.; Zee, Benny Chung-Ying; Cheung, Foon Yiu; Kwong, Philip; Chiang, Chi Leung; Leung, Kwong Chuen; Siu, Steven W.K.; Lee, Conrad; Lai, Maria; Kwok, Chloe; Chong, Marc; Jolivet, Jacques; et al.
Abstract : Objectives: This multicenter, randomized, open-label, phase II trial evaluated the efficacy and safety of AEG35156 in addition to sorafenib in patients with advanced hepatocellular carcinoma (HCC), as compared with sorafenib alone. Methods: Eligible patients were randomly assigned in a 2:1 ratio to receive AEG35156 (300 mg weekly intravenous infusion) in combination with sorafenib (400 mg twice daily orally) or sorafenib alone. The primary endpoint was progression-free survival (PFS). Other endpoints include overall survival (OS), objective response rates (ORR), and safety profile. Results: A total of 51 patients were enrolled; of them, 48 were evaluable. At a median follow-up of 16.2 months, the median PFS and OS were 4.0 months (95% CI, 1.2-4.1) and 6.5 months (95% CI, 3.9-11.5) for combination arm, and 2.6 (95% CI, 1.2-5.4) and 5.4 months (95% CI, 4.3-11.2) for sorafenib arm. Patients who had the study treatment interrupted or had dose modifications according to protocol did significantly better, in terms of PFS and OS, than those who had no dose reduction in combination arm and those in sorafenib arm. The ORR based on Choi and RECIST criteria were 16.1% and 9.7% in combination arm, respectively. The ORR was 0 in control arm. One drug-related serious adverse event of hypersensitivity occurred in the combination arm, whereas 2 gastrointestinal serious adverse events in the sorafenib arm. Conclusion: AEG35156 in combination with sorafenib showed additional activity in terms of ORR and was well tolerated. The benefit on PFS is moderate but more apparent in the dose-reduced subgroups.